2017
DOI: 10.1002/hed.24990
|View full text |Cite
|
Sign up to set email alerts
|

Ethmoidal adenocarcinoma treated by exclusive endoscopic approach: Focus on learning curve and modification of management

Abstract: Background: The purpose of this study was to investigate the outcome and recurrences for ethmoidal adenocarcinomas treated by exclusive endoscopic surgery in curative intent and investigate the role of the learning curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For example, studies performed on the NCDB database have shown that the survival of patients with squamous cell carcinoma of the nasal cavity is increased in the center with a large track record of this type of disease [140] and that centers treating more than two patients per year were associated with a higher rate of clear margins [42]. It has been shown that surgical experience may be associated with increased overall survival and local control in patients treated endoscopically for sinonasal adenocarcinoma [92,141]. Similarly, several retrospective studies have shown a decrease in CSF leak rates after endoscopic skull base reconstruction with increased surgeon experience [142,143].…”
Section: Surgeon-related Criteriamentioning
confidence: 99%
“…For example, studies performed on the NCDB database have shown that the survival of patients with squamous cell carcinoma of the nasal cavity is increased in the center with a large track record of this type of disease [140] and that centers treating more than two patients per year were associated with a higher rate of clear margins [42]. It has been shown that surgical experience may be associated with increased overall survival and local control in patients treated endoscopically for sinonasal adenocarcinoma [92,141]. Similarly, several retrospective studies have shown a decrease in CSF leak rates after endoscopic skull base reconstruction with increased surgeon experience [142,143].…”
Section: Surgeon-related Criteriamentioning
confidence: 99%
“…Finally, endoscopic endonasal surgery has consistently shown similar efficiency in tumor control and less morbidity, leading to reduced hospital stay compared with open surgery [16,19,20], although a surgical learning curve is observed [21,22]. Advances in in-…”
Section: Toward Endoscopic Resectionmentioning
confidence: 99%
“…Finally, endoscopic endonasal surgery has consistently shown similar efficiency in tumor control and less morbidity, leading to reduced hospital stay compared with open surgery [16,19,20], although a surgical learning curve is observed [21,22]. Advances in in-room imaging using surgical navigation systems can help surgeons peroperatively [23] and might further improve the rate of safe margins, thus improving oncologic outcomes.…”
Section: Toward Endoscopic Resectionmentioning
confidence: 99%